Indicators of Effectiveness of Removed Dental Prostheses - Navruzova N. O.; Saidov A. A. (International Journal on Integrated Education, 2021)
The relevance of the topic. Among the reasons for the high need for orthopedic treatment with removable dentures, the leading position is still occupied by " insufficient sanitation of the oral cavity, untimely access of patients to the dentist." In addition, an important role is played by the problem of imperfection of materials and technologies used for the manufacture of dentures, leading to deterioration of the dental system [1.3.5.7.9].